The case report of an Anaphylaxis occurred when using Sweet Bee Venom and common Bee Venom at the same time - Chaewon Kim; Yeonhee Lee; Kwangho Lee (Korean Pharmacopuncture Institute, 2011)
Objectives: The purpose of this case report are to introduce an Anaphylaxis occurred when using Sweet Bee Venom (SBV) and common Bee Venom (CBC) at the same time and a risk when used SBV and CBC together without skin test. Methods: A patient, an Anaphylaxis occurred when treated her with SBV and CBC at the same time without additional skin test, we observed the progress of the Anaphylaxis with care for her. Results & Conclusions: The Anaphylaxis in the patient was taken a turn for the better by emergency response. Based on this case, Sometimes the use of SBV and CBC at the same time without skin test can be dangerous, and to avoid the risk when used CBC together, in advance allergy test should be conducted.